Results of the First Large-Scale Survey of Transportation Network Companies Use in the Bay Area. Issue 7 (July 2022) - Bradley, Mark; Greene, Elizabeth; Sana, Bhargava; Cooper, Drew; Castiglione, Joe; Israel, Shimon; Coy, Christopher
Transportation network companies (TNCs) such as Uber and Lyft have grown tremendously over the last decade, particularly in the San Francisco Bay Area. Nonetheless, relatively little publicly available data exist about the users of these services, their travel behaviors, volume of use, the times and locations of TNC trips, and how TNC services are affecting transportation system performance overall. This paper describes the methods and descriptive results of the first large-scale smartphone-based TNC user survey conducted in the California Bay Area in the fall 2018 and spring of 2019.